1992
DOI: 10.1136/hrt.68.9.272
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear magnetic resonance spectroscopy of excised human hearts

Abstract: Background-Phosphorus nuclear magnetic resonance spectroscopy has been proposed as a method of studying the metabolism of the myocardium in patients. Little is known about 31P nuclear magnetic resonance spectroscopy of diseased human hearts.Methods-Two donor hearts meeting the requirements for heart transplantation and 11 diseased hearts were removed during a transplantation procedure and were studied in a horizontal 2-35 T superconducting magnet. Spectra were obtained at 0°C about 30 minutes after the excisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…Our data are complementary to NMR measurements, which allow determination of in vivo PCr concentration but are not capable of quantifying total creatine pool. NMR studies have previously demonstrated decreased PCr/ATP ratio in patients with heart failure [8–10,24, 25] and in patients with hypertrophic cardiomyopathy [26], which together with our results suggest that low PCr/ATP ratio is a consequence of creatine pool depletion. A low creatine pool was previously demonstrated in failing human myocardium [27].…”
Section: Discussionsupporting
confidence: 86%
“…Our data are complementary to NMR measurements, which allow determination of in vivo PCr concentration but are not capable of quantifying total creatine pool. NMR studies have previously demonstrated decreased PCr/ATP ratio in patients with heart failure [8–10,24, 25] and in patients with hypertrophic cardiomyopathy [26], which together with our results suggest that low PCr/ATP ratio is a consequence of creatine pool depletion. A low creatine pool was previously demonstrated in failing human myocardium [27].…”
Section: Discussionsupporting
confidence: 86%